Analisis Manajemen Sumber Daya Manusia Guna Mendukung Kinerja Operasional Petugas Apron Movement Control (AMC) di Bandar Udara Internasional Sultan Hasanuddin Makassar - Putri Salsabilla; Raden Ibnu Haitam (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Sultan Hasanuddin International Airport Makassar is the most crowded airport and serves flights throughout Indonesia and is connected to airports in other major cities. This certainly makes the airport require competent and qualified resources so that they can support the performance of each operational activity at the airport. This study aims to determine the quality of Apron Movement Control Officers based on human resource management analysis and to find out how Apron Movement Control officers can support operational performance at Sultan Hasanuddin International Airport Makassar. This study uses a qualitative method, namely through interviews, observations, and documentation of the Apron Movement Control (AMC) personal unit. The study was conducted for one month at Sultan Hasanuddin International Airport Makassar. The results of this study are that AMC Officers at Sultan Hasanuddin International Airport Makassar can be said to be quite qualified because several components in HRD including recruitment, training, and mentoring, work discipline, and abilities and expertise have been implemented, but it can be seen that there is still a lack of responsibility in punctuality and less than optimal handling of existing problems. To minimize problems like before, AMC officers must recruit and pay more attention to the applicable SOP. That way, operational activities at Sultan Hasanuddin International Airport Makassar can run well.